Technical Perspective Data Races are Evil with No Exceptions. - Adve, Sarita (Communications of the ACM, 2010)
The article examines the phenomenon of data races in computer programming. The author urges that computer languages that allow for data races complicate communication and synchronization. Specifically discussed are memory models associated with the programming languages C and C++ which specify undefined behavior for programs with data races.